Conceptual Foundation of Framing, Media Framing, and Rhetorical Scholarship - Sharma, Balkrishna; Pokharel, Bishnu Prasad (Literary Studies, 2025)
This article seeks to situate the concepts of framing in the rhetorical act of communication domain. The article's objective is to expand the application of framing analysis in the context of rhetorical criticism and perspectives. It argues that given the contemporary multimodal mode of communication, there is a necessity to expand the horizon of the understanding of rhetoric and rhetorical criticism. Methodologically, the article is designed on qualitative research patterns to understand an in-depth relationship between frames and rhetoric. Anchored to this theme and method, the article is structured on a three-fold pattern: first, it spells out the fundamentals of what counts as frame, showing its disciplinary orientation; second, it delineates its philosophical lineage, and third, it sketches out how the concept of framing can be profitably used to grasp the impact of rhetoric in the complex system of multidimensional human communication. In the ever-expanding and unprecedented burgeoning of communication system, it has become increasingly necessary to adopt a new lens to account for the diversities of rhetorical situations as the ancient or classical methods/approach has become too narrow and failed to capture diverse gateway of rhetorical communication.